Feasibility of data extraction and evaluation with BeoNet-Halle: outcomes and data quality in hepatitis B and C screenings - Moser, Konstantin; Bauch, Felix; Brütting, Christine; Frese, Thomas (Frontiers in Medicine, 2025)
BackgroundTo support the global hepatitis strategy, the Federal Joint Committee in Germany introduced a one-time hepatitis screening within the “Check-Up 35” program on 1 October 2021. Targeting individuals aged 35 and older, this preventive check-up aims to detect common diseases early. This study examines the feasibility of using the BeoNet-Halle database to characterize patients screened for hepatitis B (HBV) and hepatitis C virus (HCV), focusing on screening volumes, billing codes, and data completeness.MethodsWe analyzed electronic medical records from all 11 practices contributing to the BeoNet network during the observation period from 1 October 2021 to 30 September 2023. The analysis focused on antibody and antigen tests, HBV-DNA and HCV-RNA tests, and billing codes (01734, 01744, 01865, 01866, 01867) to assess screening volumes, data completeness, and costs. Data completeness was evaluated by mapping the BeoNet dataset to the Medical Informatics Initiative (MII) Core Dataset.ResultsOf the potentially eligible population (32,213 patients aged ≥ 35), 10% underwent HBV and HCV screening as part of Check-Up 35. Screened individuals had more practice contacts (mean ± SD: 22.1 ± 19.8 vs. 11.1 ± 17.7; w = 0.3) and more chronic conditions (mean ± SD: 6.9 ± 5.6 vs. 5.8 ± 6.2; w = 0.03) than the eligible practice population. Screening identified 20 new cases (0.6%), with practice-level screening rates ranging from 2.5% to 42.6%. Billing code 01734 was documented in 81.5% of cases with laboratory test billing codes (01865–01867) missing in 5 of the 11 practice management systems (PMS). The BeoNet laboratory dataset provided full coverage for test identifiers (100%) and strong documentation of result interpretations (98.7%), but had limited coverage for reference range (60.4%) and test collection dates (9.1%).ConclusionImproving data quality and billing documentation in the BeoNet database could enhance screening accuracy and resource allocation, supporting better outcomes in hepatitis screening practices.